The Construction of Ibnu Hazm al-Andalusiy’s Holistic-Integrative Curriculum: Addressing the Problem of the Dichotomy of Knowledge in Contemporary Islamic Education - Abdullah Safa (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2026)
Ibnu Hazm al-Andalusiy is widely known as a prominent fiqh scholar of the Zhahiri School, which has led to a lack of research on his educational thoughts, particularly regarding the curriculum. Meanwhile, his educational ideas hold significant urgency amidst the current dichotomy of modern education. This study aims to analyze Ibnu Hazm's concept of the Islamic educational curriculum and its relevance to contemporary education. This study used a qualitative library research approach with a historical method to analyze primary works of Ibnu Hazm, such as Risalah Maratib al-'Ulum and Al-Akhlaq wa As-Siyar. The results indicate that Ibnu Hazm formulated a curriculum with a holistic-integrative-spiritual approach. He emphasized the commencement of formal education at the age of five, starting with basic literacy materials (reading and writing). Furthermore, his curriculum strictly integrates religious and worldly sciences. He did not place Sharia sciences at the end; rather, he made them the core axis studied concurrently with supporting exact sciences (mathematics, astronomy, logic, and medicine). In conclusion, Ibnu Hazm's curriculum concept is highly relevant to contemporary Islamic education, serving as an alternative solution to bridge the dichotomy of knowledge and comprehensively build students' characters.